Conformance of some locally available fabrics to Japan's prescribed limits on formaldehyde content - Vitug, Bernadette C.
The objectives of this research are to verify whether some locally available fabrics contain formaldehyde and if they do, conform to the prescribed limits of formaldehyde content set by Japan. Six locally available fabric samples that fall under any of the following: (1) Fabric commonly used for baby's clothing, bedding, etc. (2) Fabric identified as cotton, and Fabric which irritates the nose and eyes upon contact, were selected. They were tested for Fiber Content identification, Formaldehyde Content Analysis and patch test. Four out of the six fabric samples were identified as cotton and thus qualified for further analysis. Formaldehyde Content Analysis revealed that no formaldehyde was detected in any of the fabric samples. The fabric samples conformed to the prescribed limits of formaldehyde set by Japan. All persons subjected to the placebo or the washed fabric samples did not experience any reaction to the sample materials. However, three persons subjected to the unwashed fabric samples experienced very slight erythema (redness) to three fabric samples. Based on the findings, samples studied were considered safe for consumer use in terms of formaldehyde content. Although some test subjects experienced skin reactions to Samples 1;4 and 6, the number of affected subjects were low and the degree of reaction was relatively mild to be considered as significant.